BATAS WAKTU WARGA NEGARA ASING MELEPASKAN HAK MILIK YANG DIPEROLEH KARENA PEWARISAN - Ibnu Maulana Muhammad; Sri Setyadji (Gapenas Publisher, 2023)
The state in addition to controlling is also obliged to regulate all natural resources of Indonesia with the aim of prosperity of the people. In the task of regulating that the state through the government also determines the right to land for its people, one of which is property rights. Individually this right can only be owned by Indonesian citizens. The attitude by renouncing Indonesian citizenship makes this affect the deadline for acquiring land rights due to inheritance. The 1-year deadline normatively does not provide legal certainty and is not an expectation. The research used is normative research, which describes and explains the core of the problem sourced from existing legal rules such as the UUPA, the Citizenship Law and other related regulations. With this method, it can provide a solution to determine the start of a 1-year deadline by the UUPA for heirs who have renounced Indonesian citizenship to transfer their property rights. Land registration in principle in addition to providing legal certainty is also of course to meet the principle of publicity. Through this means of land registration can be a sure way out against the determination of that time limit while respecting the civil rights of the heirs